2018
DOI: 10.1063/1.5023748
|View full text |Cite
|
Sign up to set email alerts
|

Ions, metabolites, and cells: Water as a reporter of surface conditions during bacterial growth

Abstract: Surface-specific nonlinear vibrational spectroscopy, combined with bulk solution measurements and imaging, is used to study the surface conditions during the growth of E. coli. As a result of the silica high surface charge density, the water structure at the silica-aqueous interface is known to be especially sensitive to pH and ionic strength, and surface concentration profiles develop that can be appreciably different from the bulk solution conditions. We illustrate that, in the presence of growing cells, a u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 82 publications
(104 reference statements)
1
21
0
Order By: Relevance
“…Moreover, when the same E. coli fractions were monitored with SFG spectroscopy, but with the cells removed, only samples from the late exponential and stationary phases showed an increase in interfacial water signal. 11 These fractions contain EPS with a higher uronic and nucleic acid content, and therefore have a greater capacity to sequester ions from the surface microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, when the same E. coli fractions were monitored with SFG spectroscopy, but with the cells removed, only samples from the late exponential and stationary phases showed an increase in interfacial water signal. 11 These fractions contain EPS with a higher uronic and nucleic acid content, and therefore have a greater capacity to sequester ions from the surface microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…The third case, the bacterium adheres to the surface and then begins secreting EPS that attract other bacterium to adhere to the surface. These models have been investigated using nonlinear vibrational spectroscopy, where recently it was discovered that the interfacial water above silica substrate appears to be change over the stages of bacterial growth, suggesting that changes in the microenvironment may play a role in bacterial adhesion [14,15].…”
Section: Adhesion Modelsmentioning
confidence: 99%
“…A motivation for this imaging study was to complement previous nonlinear vibrational spectroscopy work that suggested that the interfacial water between water-silica, the bacterial microenvironment, are sensitive to microenvironment changes during this 24 h growth period [14]. The same spectroscopy experiment was done with only bulk media, which the bacteria were grown in, over time, to determine whether factors contributed by changing bulk media, had an impact.…”
Section: Cell Adhesion At the Microenvironment Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…As is well known, water plays a key role in mediating molecular interactions at silica surfaces [19]. Experimental and theoretical studies of bio-inorganic hybrids are normally performed in aqueous systems because water helps preserving the structure and biologic functionality of proteins [16,35,36,37,38]. Actually, the confinement of biosystems within nanosized water aggregates is by itself of high current interest, as it has recently emerged as a new technology to experimentally detect conformational changes of protein active sites [39].…”
Section: Introductionmentioning
confidence: 99%